Zorro : man of the dead. Volume 1 - Murphy, Sean, 1980- (Massive Publishing, 2024)
Don Quixote meets Narcos in Sean Gordon Murphy's Zorro: Man of the Dead. In this modern reimagining, the writer-artist behind DC Comic's Batman: White Knight, delivers a fresh take on the legendary swashbuckling hero. Diego is a young man who is convinced that he's Zorro. As a child, he suffered a psychotic break after witnessing the murder of his parents by the drug cartel in his village. To cope with the trauma, he embraced the 200-year-old legend of Zorro by donning the mask, training with the sword, and declaring war on the Narcos for the sake of his people.